Mobilizing transdisciplinary collaborations: collective reflections on decentering academia in knowledge production - Alonso-Yanez, G., House-Peters, L., Garcia-Cartagena, M., Bonelli, S., Lorenzo- Arana, I.; Ohira, M. (My University, 2019)
Global sustainability challenges and their impact on society have been well-documented in recent years, such as more intense extreme weather events, environmental degradation, as well as ecosystem and biodiversity loss. These challenges require a united effort of scientists from multiple disciplines with stakeholders, including government, non-government organizations, corporate industry, and members of the general public, with the aim to generate integrated knowledge with real-world applicability. Yet, there continues to be challenges for these types of collaboration. In this commentary, we describe processes of collective unlearning that serve to decenter academia in collaborations leading to a more equitable positioning of practitioners engaged in collaborative global sustainability research.
Keywords: TD